Numerical studies on low-strain integrity testing of cast-in-place pile - Ma, Lemin; Duan, Zhiqiang; Guo, Wei; Ren, Yuxiao (Frontiers in Built Environment, 2024)
A series of in situ tests were conducted using the low-strain integrity testing method to detect the defects of cast-in-place concrete piles. Numerical studies were conducted to observe the time-domain waveform along cast-in-place concrete piles with diameter expansion, diameter reduction and segregation defects. It is found the time-domain waveforms of the pile with the diameter expansion defects have second wave troughs after the first wavelength while those with diameter reduction and segregation defects have second wave crests. However, it is difficult to use amplitudes to directly determine the length, diameter and segregation degree of the defects. The second wavelengths could be used to identify the lengths of diameter reduction and segregation defects but it is hard to identify those of diameter expansion defects. The locations of diameter reduction and segregation defects could be determined through the time of second wave crests using the linear interpolation method, and those of diameter expansion defects could be determined through the time of second wave trough.